Evaluation of the application of water kefir grains in the decolouration of solutions containg textile dye - Xavier, Ingrid Lorena Pereira; Alcides, Mayara; Barbosa, Nathália Soares; Bagagli, Marcela Pavan (Revista Brasileira de Engenharia de Biossistemas, 2022)
One of the main environmental problems presented by the textile industry is the generation of effluents containing synthetic dyes. Because of that, studies have been carried out in order to remove or degrade the dyes present in wastewater and thus, the adsorption process in polymeric matrices has been highlighted due to its low cost and high efficiency in bioremediation. In this context, it was verified the potential of biodegradation of the anthraquinone C. I. Reactive Blue 4 HFG textile dye (Dianativo®) by water kefir grains, as well as the application of the insoluble exopolysaccharide produced by the grains as an adsorbent of the dye, evaluating the effect of pH and initial concentration of dyes in the reduction of staining in a model system. The grains and their insoluble polysaccharide matrix were presented as capable of decolourizing dye solutions under the evaluated conditions, reducing the dye concentration in the solution by up to 92%.